1977
DOI: 10.2478/cttr-2013-0429
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Formation Studies: IV. The Dynamic Measurement of the AxiaI Density of a Burning Cigarette

Abstract: Much research has gone into establishing the temperature gradients that exist inside a burning cigarette. These temperature gradients should correspond to changes in the density of the tobacco column due to the condensation and subsequent re-evaporation of volatiles resulting from pyrolysis, combustion, and final ash formation. These dynamic measurements on the burning cigarette were made using a modified beta thickness gauge. A beam of collimated beta particles from a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…At the same time the cold tobacco and diluting air coming through the rod paper cause the rapid cooling and condensation of some smoke components onto the tobacco shred surfaces behind the char line. Tobacco rod density increases slightly about 2 mm behind the char line because of newly deposited condensate [9,12]. Distillation occurs mainly at and behind the char line where components may volatilize at temperatures above 150 • C [13].…”
Section: Physical and Chemical Events In The Cigarette Puff And Smoldmentioning
confidence: 99%
“…At the same time the cold tobacco and diluting air coming through the rod paper cause the rapid cooling and condensation of some smoke components onto the tobacco shred surfaces behind the char line. Tobacco rod density increases slightly about 2 mm behind the char line because of newly deposited condensate [9,12]. Distillation occurs mainly at and behind the char line where components may volatilize at temperatures above 150 • C [13].…”
Section: Physical and Chemical Events In The Cigarette Puff And Smoldmentioning
confidence: 99%
“…The X-rays did reveal an abrupt change in the density near the coal which the authors attributed to distillation and recondensation of the volatile components. Another method was the beta ray attenuation technique developed by jENKINS et al to study the axial density changes in a burning cigarette (2). The authors were able to correlate the density changes occurring during smoking with the reported temperature profiles in the rod.…”
Section: Introductionmentioning
confidence: 99%
“…The reevaporation of condensables was attributed to either an increase in tobacco temperature or a change in the relative humidity of the atmosphere over the tobacco by the diffusion of water from the rod. Resolving a single puff and its condensation of volatiles, }ENKINS et al (114) concluded that it appeared that water was uniformly distributed within the 35 ml puff volume.…”
Section: Cigarette-rod Density Measurementsmentioning
confidence: 99%
“…Gadolinium salts have been shown to be excellent markers or tracers for individual tobaccostrand visualization. As discussed earlier, density measurements have been made in a burning cigarette and changes in the density behind the coal were observed and these density changes correlated with the temperature gradients in the cigarette (114). GoLDRING (119) used X-ray radiography to examine cigarette rods where visible variations in density of the tobacco were observed.…”
Section: J Neutron Radiographymentioning
confidence: 99%
See 1 more Smart Citation